Role of Differential Nutrient Management on Growth and Yield Attributes of Cashew (Anacardium occidetale L.) in Maidan Tracts of Karnataka - Rajendra, B. N.; Ramachandra, R. K.; Reddy, Ashwathnarayana N.; Honnabyraiah, M. K.; Vishnuvardhana; Jagadeesh, S. L.; Reddy, Anjaneya B.; M., Ramesh,; Subramanyam, B. (International Journal of Bio-resource and Stress Management, 2023)
The research on Nutrient Management for yield maximization in Cashew was conducted under Crop management, All India Co-ordinated Research Project (AICRP) on Cashew at Horticulture Research and Extension Centre, Hogalagere, Kolar district, Karnataka state, India during the period of 2020–21. There were six treatments imposed in the experiment, among the treatments, treatment-5 (T5) i.e ., cashew trees imposed with 100% RDF (500:250:250 g)+10 kg FYM along with foliar spray of major nutrients (3% Urea+0.5% MAP+1% K2SO4), secondary and micronutrients (0.5% ZnSo4+0.1% solubor as boron+0.5% MgSo4) was found significantly superior over remaining treatments in terms of growth parameters like Stem girth (17.91 cm), Canopy height (2.66 m), Canopy spread (E-W : 7.08 m except T4 and N-S : 7.12 m), Mean canopy diameter (7.10 m), Canopy surface area (158.55 m2 ) and ground area covered by plant canopy (61.99%). Whereas, T5 was also recorded significantly superior over other treatments and followed similar trend as in growth attributing parameters, such as Nut yield per tree (14.50 kg), Yield per hectare ( 18.87 q), Cumulative nut yield for six years of harvest (56.82 kg) and Cumulative yield per hectare (88.64 q). However the treatment-5 was also numerically elevated higher values in remaining all parameters and the lowest observation values were found in T6 (control). When look at the overall performance, treatment-5 (T5) was found to be best treatment.